2009
DOI: 10.1038/ki.2008.578
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline attenuates interstitial inflammation and ameliorates the progression of renal fibrosis

Abstract: Amitriptyline is a pleiotropic tricyclic antidepressant, which has anti-oxidant and anti-inflammatory properties. We tested whether amitriptyline might be useful in the treatment of chronic renal disease using the mouse model of unilateral ureteral obstruction. Amitriptyline caused a significant reduction of interstitial fibrosis, determined by Masson's staining, with minimal myofibroblast formation and macrophage infiltration following ureteral obstruction. Using quantitative PCR we found that this treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Similarly, inhibition of ASM activity has also been shown to render cells and animals resistant to the apoptotic effects of diverse stimuli including Fas/CD95 [5], ischemia [6], radiation [7], chemotherapy [8] tumor necrosis factor-alpha (TNF-α) [9]. In addition, Asm knockout or Asm inhibition was shown to have protective action during the lung inflammation and fibrosis [10], cystic fibrosis [11][12], obesity and associated glomerular injury [13], liver fibrogenesis [14] and renal fibrosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, inhibition of ASM activity has also been shown to render cells and animals resistant to the apoptotic effects of diverse stimuli including Fas/CD95 [5], ischemia [6], radiation [7], chemotherapy [8] tumor necrosis factor-alpha (TNF-α) [9]. In addition, Asm knockout or Asm inhibition was shown to have protective action during the lung inflammation and fibrosis [10], cystic fibrosis [11][12], obesity and associated glomerular injury [13], liver fibrogenesis [14] and renal fibrosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…2009). Although this drug is not indicated in patients undergoing bladder outlet obstruction, recent studies have reported the anti‐inflammatory and muscle relaxant effects of amitriptyline hydrochloride (Achar et al. 2003, 2009), which has been already used clinically to alleviate disorders of the urinary system, such as enuresis, interstitial cystitis and detrusor instability, and to induce the extrusion of urinary calculi.…”
mentioning
confidence: 99%
“…Within this context, amitriptyline, the object of the present study, in addition to inhibiting monoamine reuptake, is well known to present antimuscarinic, antihistaminergic (H 1 ) and ␣ 1 -adrenergic antagonist effects [4,5,15] . The last action was related to vasodilation and consequent hypotension observed at the beginning of the treatment.…”
mentioning
confidence: 99%